2009
DOI: 10.1249/jsr.0b013e3181b7f042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Assessment for Superior Labrum Anterior and Posterior Lesions

Abstract: In the evaluation of the painful shoulder, especially in the overhead athlete, diagnosing superior labrum anterior and posterior (SLAP) lesions continues to challenge the clinician because of 1) the lack of specificity of examination tests for SLAP; 2) a paucity of well-controlled studies of those tests; and 3) the presence of coexisting confounding abnormalities. Some evidence indicates that multiple positive tests increase the likelihood that a SLAP lesion is present, but no one physical examination finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…A pain pattern described as posterior-superior or deep within the anterior-superior glenohumeral joint may reflect a SLAP lesion. 18,19 SOR: C 3. Throwing athletes who present with posterior shoulder tightness (loss of .158 horizontal adduction or a glenohumeral internal-rotation deficit [GIRD] of .138 to 158 without a concurrent increase in ER of .158 as compared with the nonthrowing shoulder) should be considered to have an increased risk of shoulder injury, including a SLAP lesion.…”
Section: Recommendations Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…A pain pattern described as posterior-superior or deep within the anterior-superior glenohumeral joint may reflect a SLAP lesion. 18,19 SOR: C 3. Throwing athletes who present with posterior shoulder tightness (loss of .158 horizontal adduction or a glenohumeral internal-rotation deficit [GIRD] of .138 to 158 without a concurrent increase in ER of .158 as compared with the nonthrowing shoulder) should be considered to have an increased risk of shoulder injury, including a SLAP lesion.…”
Section: Recommendations Diagnosismentioning
confidence: 99%
“…2 This mechanism could also result in other shoulder injuries, such as a rotator cuff tear or anterior instability. 2,18 A chronic SLAP lesion more commonly affects athletes in repetitive overhead sports such as baseball, softball, volleyball, and tennis. 3 Hypothesized mechanisms of injury include tension, torsion, and eccentric loads to the biceps during sport activities that injure the biceps-labral complex.…”
Section: History Observation and Palpationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are tests that are helpful in the diagnosis, physical examination and history are not useful for definitive diagnose of a SLAP lesion. Reports in the literature describe at least 26 maneuvers as useful in helping to make the diagnosis of a SLAP lesion [5,6] Cook et al [7] reported that the strongest positive predictive value and negative predictive value of the these tests were provided by the Kim Test II and the Labral Tension test.…”
Section: Discussionmentioning
confidence: 99%